Luteolin Enhances Choroid Plexus 5-MTHF Brain Transport to Promote Hippocampal Neurogenesis in LOD Rats - Li, Hui-Zhen; Liu, Kai-Ge; Zeng, Ning-Xi; Wu, Xiao-Feng; Lu, Wen-Jun; Xu, Han-Fang; Yan, Can; Wu, Li-Li (Frontiers in Pharmacology, 2022)
Context: Folates, provided by food, is a commonly used antidepressant synergist in Late-onset depression (LOD). However, increased intake of folic acid in the elderly population might lead to accumulation of unmetabolized folic acid in the systemic circulation enhance a deterioration of central nervous system function. In addition, folates cannot achieve the brain directly, owing to the blood-brain barrier. Choroid plexus 5-MTHF brain transport plays a critical role in CSF 5-MTHF content. Luteolin, a natural flavonoid that has anti-depressant effects, and is involved in the anti-folate resistance pathway. It remains unclear whether luteolin anti-depressants are associated with choroid plexus 5-MTHF brain transport. Method：20-21-month-old Wistar rats were exposed to the CUMS protocol for 6 consecutive weeks to explore the long-term effects of luteolin on behavior, 5-Methyltetrahydrofolate (5-MTHF) lever, hippocampal neurogenesis, and folate brain transport of Choroid plexus. In vitro, investigated the effects of luteolin on the primary hippocampal neural stem cells (NSCs) and choroid plexus epithelial cells (CPECs) under CORT+D-gal conditions. Results: We found that AGED rats exposed to CUMS showed significantly reduced sucrose preference, locomotion activity level of OFT and accuracy of MWMT, increased immobility time, reduced the number of BrdU/DCX，Ki-67/Nestin and NeuN-positive cells in the hippocampus, as well as decreased CSF and hippocampus 5-MTHF levels, ZO-1, PCFT, and RFC protein expression. In vitro assays showed 10% AGED-CSF and luteolin - CSF significantly increasing CORT+ D-gal-injured NSCs viability, the number of BrdU/DCX-positive NSCs compared with the CORT+ D-gal group. Nevertheless, 10% LOD-CSF had no such effect. In the meantime, induction of CORT+D-gal significantly decreased the ZO-1, PCFT, RFC, and FR-α protein expression and trans-epithelial electrical resistance (TEER) in rats CPECs. As expected, luteolin treatment is effective in improving these abnormal changes. Conclusions: These findings suggested that luteolin could ameliorate CUMS-induced LOD-like behaviors by enhancing folate brain transport.